026 Applying a child/young person-centred approach to develop vision-related quality of life (VQOL) and functional vision (FV) instruments for children/young people. (December 2018) - Robertson, A; Tadic, V; Rahi, JS
Abstract : Introduction: Developmentally sensitive measures of vision-related quality of life (VQoL) and functional vision (FV) are needed to capture age-specific concerns about the impact of living with visual impairment (VI) during childhood and adolescence. We report a child/young person-centred approach to adapting our validated VQoL and FV instruments for visually impaired children aged 10–15 years to a broader age-range of children and young people (YP). Participants were children and YP aged 7–19 years with VI (acuity worse than 0.48 logMAR) attending Great Ormond Street Hospital and Moorfields Eye Hospital, London, supplemented, in the final phase, by patients attending 20 further UK hospitals. The study followed standard phases of questionnaire development comprising of qualitative interviews with participants to inform age-appropriate modifications to questionnaire content and formats and questionnaire administration via postal survey to pilot and evaluate the instruments. Rasch analysis was applied to assess instruments' psychometric performance and calibrate age-specific versions. Results: Qualitative interviews informed minor modifications to the existing instruments to address age-specific needs, resulting in two age-appropriate extensions: one for children aged 8–12 and the other for YP aged 13–17 years. The VQoL_Child, FV_Child, VQoL_YP and FV_YP instruments comprise 20-, 28-, 22-, and 38-items respectively, with 12 VQoL and 24 FV overlapping 'core' items across the extensions. Discussion/conclusion: Age-appropriate versions of VQoL and FV instruments have been calibrated to enable comparisons across different ages, whilst retaining age-specific content. These instruments have a wide application in research and clinical practice (e.g. in trials evaluating vision-specific treatments, or longitudinal follow-up, of children/YP aged 8–17 years), whilst maintaining specificity to developmental nuances of childhood and adolescence.